Association Of Nonadherence And Beliefs About Medicines Among Hemodialysis Patients In Penang - Lee, Soik Fun (2022)
Medication nonadherence (MNAD) among hemodialysis patients can be caused by erroneous medication beliefs. However, assessment on hemodialysis patients’ beliefs about prescribed medicines is not routinely conducted in Malaysia. This study aimed to assess the prevalence of MNAD among hemodialysis patients and the association between patient’s beliefs about medicines and MNAD. This was a cross-sectional multicentre study among hemodialysis patients conducted in Penang by purposive sampling. Data was collected by using 5 items-medication adherence report scale (MARS-5) and Beliefs about Medicine questionnaire (BMQ). Multiple logistic regression was used to assess the association of MNAD with beliefs about medicines. A total of 325 patients were interviewed. Majority patients were aged 55 years or more (69.0%) and received 6-10 prescribed medications daily (58.2%). The prevalence of MNAD was 69.5% based on MARS-5 score. Considering the BMQ score, the median score for Specific–Necessity and Specific–Concerns domain was 19.00 (17.00-20.00) and 12.00 (11.00-16.00) respectively. Whereas, the General–Overuse and General–Harm domain showed total mean score of 11.00 (10.00-12.00) and 9.00 (8.00-10.00) respectively. The patients with belief of medication will protect them from becoming worse showed significant less MNAD (adjusted OR = 0.543, CI = 0.366, 0.903).